A Note on McPherson Number of Graphs - Susanth, C.; Kalayathankal, Sunny Joseph; Sudev, N. K. (Journal of Informatics and Mathematical Sciences, 2016)
By the explosion of a vertex \(v\) in a graph \(G\), we mean drawing edges from \(v\) to all other vertices in \(G\) that are not already adjacent to it. The recursive concept of vertex explosions is called the McPherson recursion. The McPherson number of a graph is the minimum number of vertex explosions required in \(G\) so that the resultant graph becomes a complete graph. In this paper, we determine the McPherson number of a given graph.